The many faces of King Gesar Tibetan and Central Asian studies in homage to Rolf A. Stein - Kapstein, Matthew T. 1949-; Ramble, Charles 1957- (Brill, 2022)
"The Tibetan Gesar epic, considered "the world's longest poem," has been the object of countless retellings, translations, and academic studies in the two centuries since it was first introduced to European readers. In The Many Faces of Ling Gesar, its many aspects-historical, cultural, and literary-are surveyed for the first time in a single volume in English, addressed to both general readers and specialists. The original scholarship presented here, by international experts in Tibetan Studies, honours the contributions of Rolf A. Stein (1911-1999), whose studies of the Tibetan epic are the enduring standard in this field. Contributors are: Anne-Marie Blondeau, Chopa Dondrup, Estelle Dryland, Solomon George FitzHerbert, Gregory Forgues, Frances Garrett, Frantz Grenet, Lama Jabb, Matthew W. King, Norbu Wangdan, Siddiq Wahid, Wang Guoming, Yang Enhong"
Keywords: Ge-sar-Gyi-sGrungs; Gesar / (Legendary character) / In literature; Gesar; Epic poetry, Tibetan / History and criticism; Gesar / (Legendary character); Epic poetry, Tibetan; Literature; Criticism, interpretation, etc; Essays; Festschriften; Literary criticism; Festschrift